Does Corporate Governance Affect the Corporate Performance Persistence by Economic Value Added in Listed Companies of Malaysian Stock? - Derayat, Mojgan; Banimahd, Bahman (International Review of Management and Marketing, 2020)
Corporate governance is a mechanism used to reduce the conflict of interests and agency costs. It consists of intrinsic and extrinsic mechanisms. Company ownership structure is one of the most important extrinsic mechanisms of corporate governance and shareholders are able to monitor and control the company's directors' performance enabling them to reduce the costs and increase the firm value. This study aims to check whether corporate governance effect by EVA on the corporate performance persistence in listed companies of Malaysian stock and also to investigate the corporate governance practices in the registered companies in Bursa MY and their outcome on the relationship amongst corporate productivity and the extent practicing company set of rules and mechanisms. The sample includes the top 100 companies in Malaysia (FTSE Bursa MY Top 100 Index), registered in the Bursa MY, during 2009-2013 and because it is a comparative study, the final sample consisted of 84 companies. The statistical findings suggested that there is a correlation amongst corporate governance mechanisms and performance persistence, as measured by approximate EVA. Keywords: Company Performance; Corporate Governance Practices; Economic Value Added (EVA); Malaysian stock; ownership structure. JEL Classifications: G32, G34